Interval- valued fermatean neutrosophic graphs - Broumi, Said; Sundareswaran, Raman; Shanmugapriya, Marayanagaraj; Nordo, Giorgio; Talea, Mohamed; Bakali, Assia; Smarandache, Florentin (Decision Making: Applications in Management and Engineering, 2022)
In this work, we define Interval-valued Fermatean neutrosophic graphs and present some operations on Interval-valued Fermatean neutrosophic graphs. Further, we introduce the concepts of Regular interval-valued Fermatean neutrosophic graphs, Strong interval-valued Fermatean neutrosophic graphs, Cartesian, Composition, Lexicographic product of interval-valued Fermatean neutrosophic graphs. Finally, we give the applications of Interval-valued Fermatean neutrosophic graphs.